1995
DOI: 10.1063/1.868680
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics downstream of a shallow bump: Computation and experiment

Abstract: Measurements of the velocity field created by a shallow bump on a wall revealed that an energy peak in the spanwise spectrum associated with the driver decays and an initially small-amplitude secondary mode rapidly grows with distance downstream of the bump. Linear theories could not provide an explanation for this growing mode. The present Navier-Stokes simulation replicates and confirms the experimental results. Insight into the structure of the flow was obtained from a study of the results of the calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 7 publications
4
35
1
Order By: Relevance
“…10(b)). This behavior is similar to the observation in the flow over a shallow bump studied by Joslin and Grosch (Joslin & Grosch, 1995) and the steady heating case discussed earlier. The intensity of the excess region is at the same level as that in the steady heating (compare Fig.…”
Section: Perturbed Flow By Pulsed Bumpsupporting
confidence: 73%
See 2 more Smart Citations
“…10(b)). This behavior is similar to the observation in the flow over a shallow bump studied by Joslin and Grosch (Joslin & Grosch, 1995) and the steady heating case discussed earlier. The intensity of the excess region is at the same level as that in the steady heating (compare Fig.…”
Section: Perturbed Flow By Pulsed Bumpsupporting
confidence: 73%
“…They found that the disturbance was entirely confined to the boundary layer, and the spanwise profile of the disturbance field near the bump differed dramatically from that far downstream. Joslin and Grosch (Joslin & Grosch, 1995) performed a Direct Numerical Simulation (DNS) to duplicate the experimental results by Gaster et al (Gaster et al, 1994). Far downstream, the bump generated a pair of counter-rotating streamwise vortices just above the wall and on either side of the bump location, which significantly affected the near-wall flow structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are all characterized by the formation of streamwise elongated velocity perturbations and differ in the relative position of the high and low speed streaks with respect to the roughness elements. For instance, in the experiments by Gaster et al (1994) and related simulations by Joslin & Grosch (1995); White (2002); Asai et al (2002) a region of defect velocity is formed straight behind the element. This is due to the presence of the wake, which persists downstream forming the low speed streak.…”
Section: Realizing Drag Reduction By Means Of a Passive Controlmentioning
confidence: 99%
“…At the end of the interval, (x -Xrough) /H = 120, harmonics n = 1, 2, 3, and 5, as one can see from figure 2.17, are the dominating ones, whereas the experimental [WE97] and computational [FC04] data demonstrate that the harmonics are ordered as 3, 4, 1 and 2. Another example is associated with the numerical simulation of flow behind an array of roughness elements by Joslin and Grosch [JG95]. They solved nonlinear equations for perturbations, but the boundary conditions were linearized as in Eq.…”
mentioning
confidence: 99%